Transcriptomics Profiling Identifies Cisplatin-Inducible Death Receptor 5 Antisense Long Non-coding RNA as a Modulator of Proliferation and Metastasis in HeLa Cells - Gurer, Dilek Cansu; Erdogan, İpek; Ahmadov, Ulvi; Basol, Merve; Sweef, Osama; Cakan-Akdogan, Gulcin; Akgül, Bünyamin (Frontiers in Cell and Developmental Biology, 2021)
Cisplatin is a well-known cancer chemotherapeutic agent but how extensively long non-coding RNA (lncRNA) expression is modulated by cisplatin is unknown. It is imperative to employ a comprehensive approach to obtain a better account of cisplatin-mediated changes in the expression of lncRNAs. In this study, we used a transcriptomics approach to profile lncRNAs in cisplatin-treated HeLa cells, which resulted in identification of 10,214 differentially expressed lncRNAs, of which 2,500 were antisense lncRNAs. For functional analyses, we knocked down one of the cisplatin inducible lncRNAs, death receptor 5 antisense (DR5-AS) lncRNA, which resulted in a morphological change in HeLa cell shape without inducing any cell death. A second round of transcriptomics-based profiling revealed differential expression of genes associated with immune system, motility and cell cycle in DR5-AS knockdown HeLa cells. Cellular analyses showed that DR5-AS reduced cell proliferation and caused a cell cycle arrest at S and G2/M phases. Moreover, DR5-AS knockdown reduced the invasive capacity of HeLa cells in zebrafish xenograft model. These results suggest that cisplatin-mediated pleiotropic effects, such as reduction in cell proliferation, metastasis and cell cycle arrest, may be mediated by lncRNAs.